O comportamento agressivo de crianças do sexo masculino na escola e sua relação com violência doméstica - Maldonado, Daniela Patricia Ado (Universidade Federal de São Carlos, 2003)
Aggressive behavior is one of behaviors that cause more problems to social interaction, implicating in a transgression of human rights. The present study aimed at studying aggressive behaviors of male children in school and its elation to domestic violence. For such purpose, 28 male children of low economic status, were evaluated, 14 of them showed aggression in schools (Group A) and were compared to 14 children of same sex and income who did not present aggression (Group B). Data were initially gathered by children s teachers in three elementary schools of the city of São Carlos, using the Teachers Perception of Children s Aggressive Behaviors in School Scale. Afterwards, data were alto token with the children s mothers, in their respective homes, using the Family Interview and Conflict Tactics Scale Revised . Parental consequences to children s inadequate behaviors were similar to both groups. Both parents presented health and alcohol abuse problems, but such problems were more expressive in group A. Data obtained with the Conflict Tactics Scale indicated presence of violence, in apparent contradiction to the positive evaluations about couple s relationship by mothers. General results point to the occurrence of violence in both groups, nevertheless aggressive children s group had more incidents and more severity of violence level. Final considerations signalize the need for future research in order to expand the knowledge of aggressive behavior and its relationship to domestic violence.
Keywords: Violência escolar; Crianças - comportamento agressivo; Ambiente de sala de aula; Crianças - violência doméstica; Prevenção à violência; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL